The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1037/ser0000087
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ perspectives of factors influencing implementation of evidence-based treatments in a community mental health setting: A qualitative investigation of the training–practice gap.

Abstract: The present study aimed to elucidate relations between provider perceptions of aspects of the Consolidated Framework for Implementation Research (CFIR; Damshroder et al., 2009) and provider attitudes towards the implementation of evidence-based treatments (EBTs) in an ethnically diverse community health setting. Guided by directed content analysis, we analyzed 28 semi-structured interviews that were conducted with providers during the pre-implementation phase of a larger implementation study for Cognitive Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 62 publications
4
41
0
Order By: Relevance
“…In addition to the organisational context construction and personal capacity building that were discussed in previous sections, it is crucial to promote EBP acceptance in the social work profession, which includes positive attitudes, wide adoption and scientific implementation. There are several approaches to achieve this: enhancing the curriculum in academic training, providing ongoing continuous professional training and capitalising on local opinion leaders (Marques et al., 2016). In this study, we found that personal characteristics were not significantly related to EBPA in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the organisational context construction and personal capacity building that were discussed in previous sections, it is crucial to promote EBP acceptance in the social work profession, which includes positive attitudes, wide adoption and scientific implementation. There are several approaches to achieve this: enhancing the curriculum in academic training, providing ongoing continuous professional training and capitalising on local opinion leaders (Marques et al., 2016). In this study, we found that personal characteristics were not significantly related to EBPA in China.…”
Section: Discussionmentioning
confidence: 99%
“…Although many demographic factors, such as age, gender and ethnicity, may influence practitioners' EBPA, education, training and professional experience have received more attention as factors associated with EBPA and EBP implementation (Aarons, 2005; Chonody & Teater, 2018; Marques et al., 2016; Wike et al., 2014). For social workers, EBP has been viewed as a kind of PC through which developmental and dynamic abilities are derived from continuous learning, thus allowing for the integration and application of knowledge and skills in practice in real situations (CSWE, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past 30 years, research has advanced the treatment of serious mental health disorders during childhood and adolescence such as depression, anxiety, and disruptive behavior disorders (Hoagwood et al, 2014; Mufson & Moreau, 1999). However, few research-supported treatments (RSTs) reach children in need (Marques et al, 2016; Park, Moskowitz, & Chorpita, 2018; Ringle et al, 2015). Beyond access issues-an oft cited statistic suggests that up to 65% of children and adolescents with serious mental health problems never access the mental health service system (Agency for Healthcare Research and Quality, 2010), and 60% of youth who initially engage in treatment drop out prematurely (Gopalan et al, 2010), RSTs are not commonly available in real-world community mental health settings (Marques et al, 2016).…”
mentioning
confidence: 99%
“…Frameworks such as Damschroder et al’s (2009) consolidated framework for implementation research (Keith, Crosson, O’Malley, Taylor, & Cromp, 2017) and Aaron and colleagues’ exploration preparation implementation sustainment model (Aarons et al, 2011) differentiate between barriers and facilitators that are external to or in the outer context of the organization and factors that are internal (or the inner context) to the setting. External factors include mental health legislature and policies, state mandates, and funding, including funding sources, costs associated with the RST, and the availability of funds (Beidas & Kendall, 2010; Marques et al, 2016; Ringle et al, 2015; Stirman, Gutner, Langdon, & Graham, 2016). An analysis of the costs associated with seven RSTs by Okamura et al (2018) ranged from over US$2,000 to as high as US$19,000 due to training, supervision, and certification: Unsurprisingly, this expense, which also includes the loss of billable hours when providers are engaged in training and supervisory activities, has been identified as a deterrent to adoption (Okamura et al, 2018; Palinkas, Saldana, Chou, & Chamberlain, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation